Tensões interseccionais e giro decolonial no fazer poético da escritora paraense Roberta Tavares - VIDAL, Claudia Valeria França (Universidade Federal do Pará, 2025)
The present thesis defends that Brazilian literature written by women is a space saturated with intersectional forces due to being transversed by social differences inherited from the violent European colonial process on the Americas. This is because as social agents interact, they engage in relations in which they seek to reach their interests exerting pressure on each other, that is, generating forces of power that take different forms in each society that can superpose enhancing one the other (Foucault, 1995). Although power is not a substance that may be retained and power relations also generate resistance movements, historical processes of domination breed forms of oppression that are more stable because they are historically prolonged and naturalized in a society, but in certain spaces the intensity they act intersectionally make them more evident (Collins 2022). Thus, the main goal of this research is to investigate the reverberation of gender, racialization and social class intersectional tensions in Roberta Tavares’s poetic practice considering her specificity as a woman and black person and quilombola living and producing literature in the state of Pará in the XXI century. To this purpose, we discuss colonial origins of gender, racialization and class oppression present in Brazilian social space constitution affecting above all racialized women such as the writer. Furthermore, we outline a diachronic panorama of the field of literature of female authorship from Pará with the aim of understanding the current context conditions that contribute to embrace or hinder the emergence of her production. Moreover, we think about Tavares’s works considering her mentioned specificity. The justification for this research in the scope of Communication studies is the perspective of literary text as an enunciative unity that integrates a communication process in dialogue with others as proposed by Gadamer (1999), Ricoeur (2010) and Bakhtin (2010). The decision to focus the investigation on Roberta Tavares’s works is due to her representativity in the scope established from an unprecedent survey conducted in the present research between 2021 and 2022 which catalogued 136 active female writers from Pará from the researcher’s pre-existing collection. The investigation was guided by a combination of the with affections (Moriceau, 2020) and intersectional research approaches and accomplished combining documental and bibliographical methodologies. Five axes of analysis were adopted, the first one concerning the materiality of the writer’s three individual books and the other focusing the poems of the artisanal book “Mulheres de Fogo”. Besides the mentioned studies, the theoretical framework was mainly composed of authors who discuss Brazilian literary historiography and gender, such as Gotlib (1998), Duarte (2004 and 2018) and Dalcastagnè (2018), coloniality and decoloniality in Latin America, such as Quijano